Differences of Student's Learning Outcomes on Redox Reaction Materials Using Cooperative Learning Model Type of Team Games Tournament Based on Question Card and Snakes and Standards Media - Ester Hartina Ria Sinaga; Manihar Situmorang; Marham Sitorus (Neolectura, 2021)
This study aims to determine the differences in the application of the Teams Games Tournament (TGT) cooperative model based on question cards and snakes and ladders on redox reaction material in class X SMA Negeri 14 Medan. The research sample consisted of two classes, namely the experimental class I was treated using snake ladder media and the experimental class II was treated using question card media. This research is a pretest-posttest control group design. This study uses a test instrument that has been tested and has been valid. Data on student learning outcomes were tested for normality and homogeneity, the results obtained by both samples were normally distributed and homogeneously distributed. Hypothesis testing was carried out using a two-party t-test with the results of this study at a significance level of 5% (α=0.05) indicating that t_(count ) > t (2.127 > 2.002) then Ho was rejected. This shows that there are differences in learning outcomes using cooperative learning models of the Teams Games Tournament (TGT) type based on question cards and snakes and ladders on redox material